The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00775-008-0399-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding by Ru(II)–bis(bipyridine)–pteridinyl complexes

Abstract: The interactions of five bis(bipyridyl) Ru(II) complexes of pteridinyl-phenanthroline ligands with calf thymus DNA have been studied. The pteridinyl extensions were selected to provide hydrogen-bonding patterns complementary to the purine and pyrimidine bases of DNA and RNA. The study includes three new complexes [Ru(bpy)(2)(L-pterin)](2+), [Ru(bpy)(2)(L-amino)](2+), and [Ru(bpy)(2)(L-diamino)](2+) (bpy is 2,2'-bipyridine and L-pterin, L-amino, and L-diamino are phenanthroline fused to pterin, 4-aminopteridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…The molecular planes in alternating stacks are oriented at 12.46 (2)° to each other; this could at least partially be due to packing constraints imposed by the slightly out-of-plane C18-methyl group (see packing diagram in Figure 2). Studies involving the non-methylated analog of the title compound have also been reported (Chen et al, 2010;Dalton et al, 2008;Gao et al, 2007;Ozawa et al, 2006) although, to our knowledge, no crystal structures of this analog have been reported.…”
Section: S1 Commentmentioning
confidence: 96%
See 1 more Smart Citation
“…The molecular planes in alternating stacks are oriented at 12.46 (2)° to each other; this could at least partially be due to packing constraints imposed by the slightly out-of-plane C18-methyl group (see packing diagram in Figure 2). Studies involving the non-methylated analog of the title compound have also been reported (Chen et al, 2010;Dalton et al, 2008;Gao et al, 2007;Ozawa et al, 2006) although, to our knowledge, no crystal structures of this analog have been reported.…”
Section: S1 Commentmentioning
confidence: 96%
“…For the possible use of metal complexes of this ligand as DNA probes, see: Gao et al (2007); Lawrence et al (2006). For studies involving the non-methylated analog of the title compound, see: Chen et al (2010); Dalton et al (2008); Ozawa et al (2006). For a related stucture, see: Ton & Bolte (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…1 Synthesis of chiral macrocyclic salen ligands S-1 0 , R-1 0 , S-2 0 , and R-2 0 . A solution of chloromethylsalicylaldehyde (B) in dry toluene (20 mmol, 20 ml) was added dropwise to a stirring solution of piperazine in dry toluene (10 mmol, 20 ml), and reaction mixture was stirred at room temperature.…”
Section: Preparation Of Ligand Precursorsmentioning
confidence: 99%
“…Since the intracellular target for a wide range of anticancer and antibiotic drugs is DNA, the binding studies of small molecules with DNA are extremely useful in understanding the drug-DNA interactions, designing new and promising drugs for clinical applications and developing sensitive chemical probes of nucleic acid structure (Dalton et al 2008;Sun et al 2008). During the last few decades, identifying small molecules that are capable of binding DNA through intercalation mode has attracted considerable interest (Dhara et al 2006).…”
Section: Introductionmentioning
confidence: 99%